2011
DOI: 10.1055/s-0030-1256770
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic red flags for the detection of high-risk serrated polyps: an observational study

Abstract: High risk serrated polyps are frequently nonpolypoid and are associated with synchronous advanced colorectal neoplasms. Advanced colorectal neoplasms may therefore be considered red flags for the presence of high risk serrated polyps. Detection, diagnosis, and treatment of high risk serrated lesions may be important targets to improve the quality of colonoscopic cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…In the present study, we found that patients with 1 LPD SP significantly more frequently had adenomas and advanced adenomas compared with patients with nondysplastic small distal or no serrated polyps, which is in line with previous data by us (5) and others (31,32). Taken together, these data suggest that older age, prior history of serrated polyps, current smoking, and nondaily/no aspirin use, as well as presence of adenomas, may define a risk phenotype which is associated with synchronous LPD SPs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we found that patients with 1 LPD SP significantly more frequently had adenomas and advanced adenomas compared with patients with nondysplastic small distal or no serrated polyps, which is in line with previous data by us (5) and others (31,32). Taken together, these data suggest that older age, prior history of serrated polyps, current smoking, and nondaily/no aspirin use, as well as presence of adenomas, may define a risk phenotype which is associated with synchronous LPD SPs.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is of relevance as it may highlight a subgroup of patients in whom multiplicity of lesions may require personalized surveillance, with regard to the frequency of examination or technique used (i.e., chromoendoscopy, either dye-based or digital-based techniques). In a previous study by our group, we found that presence of (advanced) adenomas during colonoscopic examination might be considered a "red flag" for synchronous serrated polyps (5). The SP risk score proposed in the current study extends these observations, by identifying an a priori risk profile for having 1 LPD SP.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Multiple lines of evidence suggest that the serrated pathway to colorectal cancer occurs primarily in the proximal colon. 3 Like others, [25][26][27][28] we found that patients with SPS very commonly had synchronous or metachronous conventional adenomas.…”
Section: Discussionsupporting
confidence: 79%